Communicating health and risk information among senior citizens in Bangladesh - Mohammad Aminul Islam; Monaemul Islam Sizear; Sharmin Akhtar; Monimul Huq (Intelektual Pustaka Media Utama, 2023)
The coronavirus disease-2019 (COVID-19) pandemic has affected human being in multiple ways all over the world. Senior citizens are more likely to get sick from COVID-19 compared to other age groups. Little is known about ways to deliver the messages to adult people to get the best outcome. We conducted a direct telephone/mobile phone-based cross-sectional survey among individuals who were aged >60 years old in Bangladesh. Verbal consent was taken and the snowball sampling method was used to reach the participants. This study showed that the most common sources of information about COVID-19 were family members, relatives, friends, and electronic media. Hence, 36.8% participants perceived that the media massages about COVID-19 were difficult to understand. Meanwhile, 53% participants could not understand the meanings news and information as those were presented using unknown terminologies. From the findings it can be concluded that the media messages should be communicated in a way that are context-specific and understandable, especially using more convenient terminology for better understanding for all levels of people.